OPTIMALISASI STRATEGI PEMASARAN BMT UGT CABANG KALIBARU DALAM MENINGKATKAN MINAT MENABUNG ANGGOTA - Ahmad Baihaqi; Indana Almas Azhar (International Conference on Humanity Education and Society (ICHES), 2026)
The development of the Islamic economy in Indonesia has not been fully followed by optimal interest in saving in Islamic savings products, particularly due to limited financial literacy and the effectiveness of marketing strategies. This study aims to analyze the implementation of the marketing strategy of BMT UGT Kalibaru Branch and the social, cultural, and economic factors that influence members' interest in saving. The study used a descriptive qualitative approach to gain an in-depth understanding of marketing practices and members' perceptions of Islamic savings. The results show that members' interest in saving is positively influenced by trust in Islamic principles, a personalized marketing approach, and Islamic financial education, but is not optimal due to limited literacy, marketing resources, and limited use of digital marketing. Optimizing marketing strategies and strengthening Islamic financial education that is adaptive to the community's socio-religious characteristics has been proven to increase members' trust, loyalty, and interest in saving, despite still facing challenges such as limited resources and competition with other financial institutions.